2012
DOI: 10.1111/j.1875-595x.2011.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health issues of oral health care workers in Edo State, Nigeria

Abstract: Objectives:  To assess awareness and prevalences of occupational health problems among oral health care workers in Edo State, Nigeria. Methods:  This cross‐sectional survey was conducted among oral health care workers working in two tiers of health care delivery in secondary and tertiary government‐owned dental centres across Edo State from December 2008 to February 2009. A self‐administered questionnaire was used to elicit information on demographic characteristics, awareness and prevalences of occupational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Such risk factors include instrument vibration, poor lighting conditions, poor positioning of the dental professionals when working on the patients or poor positioning of the patients [2][3][4]. The impact on the musculoskeletal system in dentistry is high, the upper extremity being especially very vulnerable [4][5][6][7][8][9]. Lietz et al [10] reviewed the prevalence of muscular-skeletal disorders (MSDs) among dental professionals in different countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such risk factors include instrument vibration, poor lighting conditions, poor positioning of the dental professionals when working on the patients or poor positioning of the patients [2][3][4]. The impact on the musculoskeletal system in dentistry is high, the upper extremity being especially very vulnerable [4][5][6][7][8][9]. Lietz et al [10] reviewed the prevalence of muscular-skeletal disorders (MSDs) among dental professionals in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…The 12-month prevalence of MSDs in the hand varies between 25.0% and 49.7% [4,9,[11][12][13][18][19][20]. Other international studies report hand complaints ranging from 8.4% to 66.7% [8,14,15,[21][22][23][24]. Other research showed that 19.2% to 50.0% of dental students develop MSDs on the hand during their studies [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…A prevalence rate of 97.5% of these disorders was reported among sonologists 5 and a prevalence of 49.7% among clinical health workers in a Nigerian tertiary health facility and 95.2% among radiologists [20,21]. Musculoskeletal disorder symptoms have also been observed among dental personnel practising in Edo State, Nigeria with wrist pain, waist pain and body pain/weakness recording prevalence of 66.7%, 76.7% and 84.4% respectively [22].…”
Section: Introductionmentioning
confidence: 99%
“…Where: n = minimum sample size required, Zα = value corresponding to the confidence level of 95% which is 1.96. p = percentage or proportion of the attribute of interest from previous study. In this case musculoskeletal disorder; q = 100-p, d = error margin (5%).A prevalence of 84.4% was gotten from a previous study [22] A semi-structured self-administered questionnaire was used as the study instrument. The questionnaire was adapted from pre-existing templates [11,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Dentists are at risk of some infectious diseases including tuberculosis, Human Immunodeficiency Virus, hepatitis B virus and hepatitis C virus infections. In addition, low back pain, hand and wrist complaints are the most common musculoskeletal problems in dentists [1,2]. They may develop contact dermatitits due to latex allergy and frequent use of dental instruments or some chemicals like disinfectants, detergents and solvents [1,3].…”
Section: Sirmentioning
confidence: 99%